CAUSES AND PREVENTION OF EPILEPSY - Amonova Zakhro Kakhramonovna; Amonova Zilola Kahramonovna (Web of Journals Publishing, 2025)
Epilepsy is a neurological disorder characterized by recurrent seizures, which are sudden, uncontrolled electrical disturbances in the brain. These seizures can vary in intensity and duration, affecting a person's mind, actions, and emotions. Understanding the causes and taking preventative measures are essential to effectively managing epilepsy.
Keywords: Epilepsy, infections, meningitis, brain, encephalitis, medical care.